Operating Performance, Market Performance and Sustainability Performance Before and After the COVID-19 Pandemic Era in Indonesia - Oktasya, Khofipa; Firmansyah, Amrie (AFEBI Economic and Finance Review, 2022)
This study examines differences in operating performance, market performance and sustainability performance before and after the covid-19 pandemic. Research data employs secondary data from financial statements and annual reports of consumer goods sector companies listed on the Indonesia Stock Exchange (IDX). Financial and annual reports are sourced from www.idx.co.id, www.idnfinancials.com and the company's official website. Based on purposive sampling, the research sample used is 92 observations of 46 companies for the 2019 observation year (before the covid-19 pandemic era) and 2020 (before the covid-19 pandemic era). This study concludes that there are no differences in operating performance and market performance before and after the covid-19 pandemic, while sustainability performance has differences before and after the covid-19 pandemic. This research suggests that the Indonesia Financial Services Authority (OJK) needs to increase supervision over the implementation of sustainability carried out by listed companies and harmonize policies on sustainability disclosure with disclosure standards that apply globally.